Experimental station Bernina at SwissFEL: condensed matter physics on femtosecond time scales investigated by X‐ray diffraction and spectroscopic methods. (15th April 2019) - Ingold, Gerhard; Abela, Rafael; Arrell, Christopher; Beaud, Paul; Böhler, Pirmin; Cammarata, Marco; Deng, Yunpei; Erny, Christian; Esposito, Vincent; Flechsig, Uwe; Follath, Rolf; Hauri, Christoph; et al.
Abstract : The Bernina instrument at SwissFEL Aramis employs laser‐pump and X‐ray‐probe techniques to selectively excite and probe the electronic, magnetic and structural dynamics in condensed matter systems on the femtosecond time scale and under extreme conditions. Abstract : The Bernina instrument at the SwissFEL Aramis hard X‐ray free‐electron laser is designed for studying ultrafast phenomena in condensed matter and material science. Ultrashort pulses from an optical laser system covering a large wavelength range can be used to generate specific non‐equilibrium states, whose subsequent temporal evolution can be probed by selective X‐ray scattering techniques in the range 2–12 keV. For that purpose, the X‐ray beamline is equipped with optical elements which tailor the X‐ray beam size and energy, as well as with pulse‐to‐pulse diagnostics that monitor the X‐ray pulse intensity, position, as well as its spectral and temporal properties. The experiments can be performed using multiple interchangeable endstations differing in specialization, diffractometer and X‐ray analyser configuration and load capacity for specialized sample environment. After testing the instrument in a series of pilot experiments in 2018, regular user operation begins in 2019.